Distinguishing Neurological Signs of Vestibular Dysfunction in Dogs: Central Vs. Peripheral Vestibular Disease - Sagare, Rajat; Balakrishnan, Gowri; Jeyaraja, Kirubakaran; Arunprasad, Arun; Senthil, Namakal Rajamanickam (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The present study was carried out in Madras Veterinary College teaching hospital in dogs presented with head tilt, nystagmus, strabismus suggestive of vestibular disease. The standard neurologic examination was performed which consisted of evaluation of mental status (level of consciousness), gait and body posture, postural reactions, and cranial nerve examination. These animals underwent various diagnostic tests and were classified as peripheral vestibular disease (n=14) and central vestibular disease (n=14). 17 dogs showed gait abnormalities among them three were non-ambulatory. A significant difference was detected between dogs with CVD and dogs with PVD in regard to percentage that were non-ambulatory and percentage that had a gait characterized by veering or leaning to 1 direction. While all dogs showed head tilt. Spontaneous resting nystagmus was observed in 21 dogs. There was a significant difference in percentage of dogs with spontaneous resting nystagmus between the CVD (n = 8) and PVD (n = 13) groups. At least 1 cranial nerve other than cranial nerve VIII was affected in 3 of 14 dogs with CVD while facial nerve affections is common with vestibular disease. There were no significant differences between groups regarding prevalences of abnormalities of segmental spinal reflexes, spinal hyperpathia, alterations in muscle tone, muscle atrophy, alterations in the cutaneous trunci reflex. Onto the conclusion results of the present study suggested that the neurologic examination, in its entirety, allowed reliable localization of peripheral versus central neurologic dysfunction across interpreters, but no individual feature of the neurological examination bore a strong relationship to the location of lesion